Contrast and Raman spectroscopy study of single- and few-layered charge density wave material : 2H-TaSe2 - Hajiyev, Parviz (2013)
In this article, we report the first successful preparation of single- and few-layers of tantalum diselenide (2H-TaSe2) by mechanical exfoliation technique. Number of layers is confirmed by white light contrast spectroscopy and atomic force microscopy (AFM). Vibrational properties of the atomically thin layers of 2H-TaSe2 are characterized by micro-Raman spectroscopy. Room temperature Raman measurements demonstrate MoS2-like spectral features, which are reliable for thickness determination. E1g mode, usually forbidden in backscattering Raman configuration is observed in the supported TaSe2 layers while disappears in the suspended layers, suggesting that this mode may be enabled because of the symmetry breaking induced by the interaction with the substrate. A systematic in-situ low temperature Raman study, for the first time, reveals the existence of incommensurate charge density wave phase transition in single and double-layered 2H-TaSe2 as reflected by a sudden softening of the second-order broad Raman mode resulted from the strong electron-phonon coupling (Kohn anomaly).